Capacity-delivery coordination in supply chains: a cost-based approach. (2018) - Chen, Lihua; Guiffrida, Alfred L.; Datta, Pratim
We develop a cost-based model considering a two-stage supply chain with a buyer ordering from a supplier. The model is constructed to coordinate the supply chain by joint decisions over delivery performance and capacity management. In this model, the supplier randomly assigns a portion of his permanent capacity to the buyer and the buyer determines his order quantity accordingly. A delivery window is used to classify deliveries as early, on-time or late and is used to evaluate the delivery performance of the supplier when delivery time is governed by a truncated normal probability density function. Numerical sensitivity analyses are presented to illustrate the significant managerial implications of this model.